2004
DOI: 10.1051/rnd:2004011
|View full text |Cite
|
Sign up to set email alerts
|

Age-related relationships between muscle fat content and metabolic traits in growing rabbits

Abstract: -This study was aimed at ascribing muscle fat accretion in growing rabbits to changes in several extra-muscular and intra-muscular metabolic pathways. At 10 wk or 20 wk of age (n = 8 per group), tissue lipid content and metabolic indicators of nutrient anabolic or catabolic pathways were simultaneously assessed in the liver, perirenal fat, the heart and the Longissimus lumborum (LL) muscle, together with plasma concentrations in energy-yielding metabolites. Lipid content significantly increased with age (P ≤ 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
5
13
0
Order By: Relevance
“…These results confirm the general view that mitochondria in skeletal muscles can undergo rapid changes as a consequence of modifications in environmental conditions (Hoppeler and Martin, 2003). Generally, muscle fat content variation has been proven to result from a reciprocal balance between catabolic and anabolic fatty acid fluxes, and cannot be assigned to one specific energy pathway (Gondret et al, 2004).…”
Section: Implications For Product Qualitysupporting
confidence: 85%
“…These results confirm the general view that mitochondria in skeletal muscles can undergo rapid changes as a consequence of modifications in environmental conditions (Hoppeler and Martin, 2003). Generally, muscle fat content variation has been proven to result from a reciprocal balance between catabolic and anabolic fatty acid fluxes, and cannot be assigned to one specific energy pathway (Gondret et al, 2004).…”
Section: Implications For Product Qualitysupporting
confidence: 85%
“…However, in some studies, neither LPL and lipogenic enzymes in cattle (Bonnet et al, 2007), nor oxidative and lipogenic enzymes in pigs were shown to be related to IMF variation. First, IMF accumulation during growth is the result of a balance between fatty acids synthesis into adipocytes and their oxidation within muscle fibres, rather than upregulation of a single pathway in mammals (Gondret et al (2004a) in rabbits, Kolditz et al (2009) in fish); the turnover of fatty acids within the muscle must be considered. This assumption has been recently confirmed with the demonstration that muscle with a high IMF content displays a low adenosine monophosphateactivated protein kinase (AMP-K) activity compared with low-fat muscle.…”
Section: How Might Marbling Begin?mentioning
confidence: 99%
“…Then, the relationships between IMF content and metabolic markers could depend on the source of variation in IMF. This is the reason why some authors have preferred to combine both blood indicators and metabolic enzyme activities to predict IMF variability, but the equations of prediction differ between muscles (Gondret et al, 2004a). Furthermore, because enzymes of the same metabolic pathway (for instance, in mitochondria) are sometimes largely unrelated (Gondret et al, 2004b), it is important to combine different metabolic markers.…”
Section: How Might Marbling Begin?mentioning
confidence: 99%
“…The development of intramuscular fat has been associated with fatty acid oxidation and ATP synthesis that occurs in muscle tissue (3). Previous studies have suggested that the intramuscular fat content in rabbits and sheep was due to a balance between catabolism and anabolism rather than a specific biochemical pathway (4,5). However, others have reported a significant correlation between intramuscular fat content and the mitochondrial enzymes cytochrome c oxidase and isocitrate dehydrogenase (6).…”
Section: Introductionmentioning
confidence: 99%